EVALUASI DINAMIKA TITIK BERAT KURSI RODA PADA KEMIRINGAN JALAN 20° BERDASARKAN SIMULASI DAN PERHITUNGAN ANALITIS - Usman; Faisal Habib; Hairun Apriadi Ramadhan; Angga Tegar Setiawan (Universitas Wahid Hasyim, 2025)
According to data from Indonesia’s Central Statistics Agency (BPS) and the Ministry of Social Affairs [1,2], over 5.3 million individuals with physical disabilities face mobility challenges, particularly when using wheelchairs on sloped terrain. A major issue is the instability of manual wheelchairs on steep inclines, which increases the risk of tipping and requires assistance. This study aims to evaluate the dynamics of center of gravity (COG) shifts in wheelchairs on road slopes up to 20°, using simulation and analytical calculation methods. The methodology includes literature review, wheelchair type surveys, slope condition observations, and system kinematics and force analysis. Results show that the COG remains within a safe zone during slope transitions, with reaction force distribution remaining stable between 87.63 and 93.26 kg. Pressure on the front and rear wheels remains within safety limits, avoiding deformation or loss of traction. The highest power consumption recorded was 144.56 watts during ascent, which significantly decreased on flat or descending terrain. The findings suggest that the proposed wheelchair design is adaptive, safe, and energy-efficient, making it suitable for users with disabilities navigating urban environments with varied topography.